2003
DOI: 10.1080/0144361031000153675
|View full text |Cite
|
Sign up to set email alerts
|

Quality of brief guidelines produced by professional bodies: a study of the 'green-top' guidelines by the UK Royal College of Obstetricians and Gynaecologists

Abstract: Clinicians ignore lengthy guidelines and prefer pocket cards and concise pamphlets. However, brevity in guidelines may lead to deficiency in quality. Our objective, therefore, was to examine the quality of brief guidelines produced by professional bodies, using those produced by the UK Royal College of Obstetricians and Gynaecologists (RCOG) as an example. We assessed all 22 'green-top' guidelines, produced by September 2002, for quality using a validated 37-item appraisal instrument. This instrument evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…The use of both appraisal instruments allowed a comparison of our data with a wide range of other published guideline reviews (see below). 3,[17][18][19][20]22,23 Although the methodological quality of current endometriosis guidelines was low, the clinical advice contained in these documents was similar, although it was not always supported by evidence possibly due to lack of quality primary research in this field. Only three of eight guidelines met at least half of the quality standards in the rigour of development domain, with low scores attributable to a lack of external expert review, details of future updates and that risks have been considered in formulation of the recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of both appraisal instruments allowed a comparison of our data with a wide range of other published guideline reviews (see below). 3,[17][18][19][20]22,23 Although the methodological quality of current endometriosis guidelines was low, the clinical advice contained in these documents was similar, although it was not always supported by evidence possibly due to lack of quality primary research in this field. Only three of eight guidelines met at least half of the quality standards in the rigour of development domain, with low scores attributable to a lack of external expert review, details of future updates and that risks have been considered in formulation of the recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…They need to be free of biases, which could not only result in the denial of best care but also lead to harmful practices. 2 Attempts to evaluate the quality of guidelines have generally shown poor adherence to the quality standards 3,[17][18][19][20] (Tables 4 and 5). This is of particular concern for guidelines produced by professional bodies as they reach a targeted audience that is generally expected to accept the recommendations as 'the standard to be achieved'.…”
Section: Discussionmentioning
confidence: 99%
“…In a guideline published by the Royal College of Obstetricians and Gynaecologists (Green‐top Guidelines No. 52), there are four components in the management of PPH, in the order of: Communication, Resuscitation, Monitoring and Investigation, and Arresting the bleed.…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines suggested that once the uterus was successfully inverted and other causes of PPH were ruled out, pharmacological and mechanical interventions should be initiated. This involved bimanual compression and injection of syntocinon, ergometrine or carboprost . Misoprostol can also occasionally be given per rectal .…”
Section: Discussionmentioning
confidence: 99%
“…As such, guidelines are not perfect; they can be extremely long and consequently may not be used, and the quality, context and applicability are sometimes criticised. [3][4][5][6] It is this area that causes contention, creates questions and suggests the need for thought. What do you do if you disagree with a guideline recommendation or approach?…”
mentioning
confidence: 99%